Xenopus paraxial protocadherin has signaling functions and is involved in tissue separation - Medina, Araceli (Nature Publishing Group, 2004)
Protocadherins have homophilic adhesion properties and mediate selective cell–cell adhesion and cell sorting. Knockdown of paraxial protocadherin (PAPC) function in the Xenopus embryo impairs tissue separation, a process that regulates separation of cells of ectodermal and mesodermal origin during gastrulation. We show that PAPC can modulate the activity of the Rho GTPase and c-jun N-terminal kinase, two regulators of the cytoskeletal architecture and effectors of the planar cell polarity pathway. This novel signaling function of PAPC is essential for the regulation of tissue separation. In addition, PAPC can interact with the Xenopus Frizzled 7 receptor, and both proteins contribute to the development of separation behavior by activating Rho and protein kinase Cα.